FRI0092 Effects of baricitinib on haemoglobin and related laboratory parameters in rheumatoid arthritis patients. (15th June 2017) - Kay, J; Harigai, M; Rancourt, J; Dickson, C; Isaka, Y; Chen, L; Carmack, T; Hyslop, D; Muram, D; Macias, W; Bradley, J; Keystone, E
Abstract : Background: Baricitinib (bari), a selective, transient and reversible inhibitor of Janus kinase (JAK)1 and JAK2, improved signs and symptoms of active rheumatoid arthritis (RA) in multiple phase 3 studies. Since erythropoietin (EPO) stimulates erythrocyte production via the JAK2 signaling pathway, haemoglobin (Hgb) and other haematologic parameters were thoroughly evaluated in the bari RA clinical development program. Objectives: To evaluate baseline and subsequent changes in Hgb and related laboratory parameters in RA patients (pts) treated with bari (2 or 4 mg once daily), placebo (PBO), or active comparator (methotrexate [MTX] or adalimumab [ADA]). Methods: Blood samples were analyzed at baseline and at each study visit for complete blood count, with more extensive phlebotomy at baseline (Wk 0) and Wks 12, 24, and 52 (Figure 1 ). Data were aggregated from completed Phase 2 and 3 RA studies and one ongoing long-term extension study. EPO and reticulocyte (RET) data were collected from a Phase 2 RA study in Japan. Results: Hgb levels below the gender-adjusted lower limit of normal (LLN) were often observed at baseline (25%). Small declines in Hgb were observed at Wk 2 and again at Wk 14 in bari (2 and 4 mg) and PBO-treated RA pts consistent with the volume and frequency of phlebotomy (Figure 1 ). Initial decreases in Hgb were accompanied by declines in RET counts in bari-treated RA pts. Subsequent increases in Hgb were associated with increases in RET after Wk 8 and statistically significant dose-dependent increases vs. PBO in total iron (Fe), total iron binding capacity (TIBC) and EPO. Treatment-emergent (TE) shifts in Hgb from normal to <LLN were very common in all groups without differences across groups except for ADA, which was associated with a lower incidence of TE low Hgb. TE Common Terminology Criteria for Adverse Events (CTCAE) shifts in Hgb from <grade 3 to ≥grade 3 (<4.9 and ≥4.0 mmol/L; <8.0g/dL and ≥6.5g/dL) were uncommon and occurred in similar proportions of RA pts across groups (Table 1 ). Permanent discontinuation of study drug due to CTCAE ≥grade 3 Hgb shifts was uncommon (0.2%). Conclusions: The proportions of RA pts with TE abnormally low Hgb did not differ significantly between bari and PBO. Reductions in Hgb, including to ≥grade 3, were generally not associated with adverse outcomes. Despite concerns about the impact of JAK2 inhibition on EPO signaling, following initial declines incident to phlebotomy, dose-dependent increases in EPO, Fe, and TIBC with return to baseline in RET and Hgb were observed with bari. This suggests that homeostatic mechanisms counterbalance the pharmacologic effect of JAK inhibition on EPO signaling and that bari treatment enhances iron utilisation markers associated with anaemia of chronic disease. Disclosure of Interest: J. Kay Grant/research support from: AbbVie, Eli Lilly and Company, Pfizer, Genentech, Roche, UCB, Consultant for: Amgen, AbbVie, BMS, Eli Lilly and Company, Genentech, GlaxoSmithKline, Janssen Biotech, Merck, Novartis, Pfizer, Samsung Bioepis, Sandoz, Roche, UCB, M. Harigai Grant/research support from: BMS KK, Eisai Ltd, Ono Pharma, Takeda Ltd, Consultant for: Eli Lilly and Company, J. Rancourt Employee of: Eli Lilly and Company, C. Dickson Employee of: Eli Lilly and Company, Y. Isaka Employee of: Eli Lilly and Company, L. Chen: None declared, T. Carmack Employee of: Quintiles, D. Hyslop Employee of: Eli Lilly and Company, D. Muram Employee of: Eli Lilly and Company, W. Macias Employee of: Eli Lilly and Company, J. Bradley Employee of: Eli Lilly and Company, E. Keystone Grant/research support from: Abbott, Amgen, AstraZeneca, BMS, Hoffmann-LaRoche, Janssen, Eli Lilly and Company, Novartis, Pfizer, Sanofi-Aventis, UCB, Consultant for: Abbott, AstraZeneca, Biotest, BMS, Crescendo Biosciene, Hoffmann-LaRoche, Genentech, Janssen, Eli Lilly and Company, Merck, Pfizer, UCB, Speakers bureau: Abbott, AstraZeneca, BMS Canada, Hoffmann-laRoche, Janssen, Pfizer, UCB, Amgen